Production of lightweight red ceramic floor tiles with addition of thermoelectric plant coal fly ash and its effect on physic mechanical properties (2019)
Fly ash obtained from coal combustion was used as a partial substitute of clay material for lightweight red ceramic floor tiles production by pressing. Raw materials were characterized by X-ray diffraction and X-ray fluorescence. The technique of molding by pressing was used for the manufacture of the prototypes, once firing, were evaluated their physical and mechanical properties (linear shrinkage, apparent density, water absorption, flexural strength). The results indicated that fly ash from the thermoelectric power plant at Termotasajero under the working conditions allow reduce the density of ceramic products with physic mechanical properties adequate for its use as ceramic tiles classified as BIIb and BIIIb.